“Leo&Giulia standing for public health”: an animated series to promote the values of public health among school-aged children. Best practices and field-trial protocol - Odone, Anna; Sgueglia, Alice Clara; Bertuccio, Paola; Vecchio, Riccardo; Meloni, Alessandro; Gianfredi, Vincenza; Traverso, Laura; Gaeta, Maddalena; Vigezzi, Giacomo Pietro (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The “Leo&Giulia standing for public health” project is an innovative digital health education model targeting primary school children. The project, developed during the COVID-19 pandemic, aims to educate primary school-aged children about public health issues through an animated cartoon series. It highlights the importance of early-life health promotion and the potential role of educational settings in shaping health behaviours. Study design. A 2-year school-based cluster-randomized controlled community trial will be conducted among 8-10-year-old pupils in the province of Pavia, Northern Italy. Methods. The intervention group will receive an educational programme via a new episode of “Leo&Giulia” animated series, focusing on smoking prevention. The study will assess changes in knowledge, attitudes towards smoking, and communication about smoking risks among peers and parents. The trial involves baseline and follow-up assessments through questionnaires targeting both children and parents. Results (expected). We assume that children in the intervention group will demonstrate increased knowledge and awareness of smoking-related health risks and develop negative attitudes towards tobacco use compared to the control group. Enhanced communication about tobacco harms among peers and between children and parents, as well as increased parental involvement in anti-smoking socialization practices, are expected secondary outcomes. Discussion and Conclusions. “Leo&Giulia” integrates health education into the school curriculum, leveraging the appeal of animated content to engage children in public health topics. The project is expected to contribute to the field of health education by demonstrating the effectiveness of digital health interventions in childhood, foreseeing potential long-term impacts on health behaviors and in shaping future public health strategies.